Dosimetric comparison of intensity modulated radiotherapy, volumetric-modulated arc therapy and tomotherapy in patients with gastric adenocarcinoma after curative surgery - Jia-Jia Zhang; Xin Wang; Jing Jin (临床与病理杂志, 2026)
Objective: To compare the dosimetric differences between IMRT, VMAT and TOMO planning for gastric cancer patients. Methods: A total of 14 patients with gastric cancer after curative surgery were prospectively enrolled. In each case, IMRT, VMAT and TOMO plans were created (45Gy/25f). Dose distributions and dose–volume histograms for PTV and normal tissue were compared. A paired t test or signed-rank test was applied to compare the averages between techniques. Results: Comparison of the PTV revealed satisfactory coverage by the 95% isodose envelope in three plans. However, significantly higher conformity index (CI) and lower V20 of bone marrow were observed in TOMO plan. Moreover, IMRT and TOMO techniques both showed significant reduced mean dose of the bilateral lungs compared to the VMAT. Not much difference was found in parameters of the kidney, intestine, spine, liver and heart. Conclusion: The IMRT, VMAT and TOMO plans all achieved favorable target coverage and dose sparing of the critical organs in adjuvant radiotherapy for gastric cancer. However, the TOMO technique displayed the best target dose conformity and superior sparing of the bone marrow and lungs.